Synthesis of MgFe2O4/WO3 Photocatalyst for Enhanced Removal of Methylene Blue from Water - Huyen, Nguyen Khanh; Hien, Le Thu; Anh, Le Quynh; Trinh, Tran Dinh (VNU Journal of Science: Natural Sciences and Technology; Vol 42 No 2DO - 10.25073/2588-1140/vnunst.5915, 2026)
In this study, a series of photocatalytic materials based on MgFe 2 O 4 and WO 3 semiconductors with various MgFe 2 O 4 /WO 3 mass ratios (1:4), (1:3), (1:2), (2:1), (3:1), and (4:1) were successfully synthesized using hydrothermal method under mild conditions. The results showed that all synthesized composites exhibited visible light absorption, with band gap energies ranging from 1.92 eV to 2.06 eV. The coupling of MgFe 2 O 4 with WO 3 significantly enhanced photocatalytic performance by effectively suppressing the recombination of photogenerated charge carriers. Among the produced composites, MgFe 2 O 4 /WO 3 (3:1) material demonstrated the most efficient charge separation, leading to excellent degradation efficiencies regarding the degradation of Methylene Blue (MB) organic dye in water. MgFe 2 O 4 /WO 3 (3:1) photocatalyst presented a MB degradation efficiency of bout 81%, corresponding to 1.64 times higher than that of pure MgFe 2 O 4 and 2.67 times greater than that of WO 3 . These results suggest that the synergy between MgFe 2 O 4 and WO 3 effectively reduces the recombination rate of charge carriers, thereby improving the photocatalytic degradation of organic pollutants. The degradation of MB followed the pseudo-second-order kinetics model, with R 2 within the range of 0.9769 - 0.9987 while HO • and O 2 •- were main reactive species responsible for MB degradation process. This finding highlights the potential use of MgFe 2 O 4 /WO 3 photocatalysts for wastewater treatment application.